Coronaviruses of the veterinary and socio-economic importance: Classification, pathogenicity, transmission, and evolution of the coronaviruses (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Most of the coronaviruses are known because they are pathogens of veterinary and economic importance or of social importance. The current knowledge on the origin, diversity, evolution of coronaviruses, as well as treatment and prevention strategies, and their impact on animal industries are discussed in this paper. The contribution factors for the outbreak of pathogenic coronaviruses and the potential of spill over of zoonotic coronaviruses to humans are also highlighted in this review paper.
Keywords: coronaviruses; classification; pathogenicity; transmission; evolution